Fixing a blurred photograph : image deblurring - Lian, Jia Jie (Nanyang Technological University, 2021)
Image blur is an unwanted product and can be formed due to many reasons such as movement during image capture, low intensity during camera exposure, atmospheric problems etc. As a result, the image is degraded and the captured scene is rendered unreadable. In order to extract useful information from a blurred image, deblurring has to be done. Recently, blur removal has become one of the most common field of image processing research and has sparked a lot of interest.